The Environmental Effects Induced by a Metro Shield Tunnel Side-Crossing on Adjacent Pile Foundations and Its Impact Partition - Hui Hu (Advances in Civil Engineering, 2021)
With the advantages of fast construction speed and small disturbance to stratum, shield tunneling is becoming the preferred construction scheme for metro construction. However, if the disturbance of stratum cannot be clearly understood, it will affect the safety of adjacent underground structures and aboveground buildings. Based on the construction of the interval tunnel between Shizishan station and Chuanshi station of Chengdu metro line 7 project, this paper proposed a simplified calculation method to analyze the impact of shield excavation on adjacent pile foundation. A two-stage method of modified Peck formula and Winkler elastic foundation model was used to investigate the additional displacement and internal force of pile. A three-dimensional numerical model validated with the field test data was performed to compare with the theoretical results. The impact factors and their impact degree were discussed. The results show that the additional displacement and internal force are at a reasonable and acceptable level. The permanent pile foundation should adopt the small diameter pile as far as possible. When the small diameter pile foundation cannot meet the stress requirements, the design scheme of the pile group should be adopted. The area around shield tunnel is divided into strong impact area of pile foundation (S ≤ 0.75 D), slight impact area (0.75 D ≤ S ≤ 1.5 D), and no impact area (S > 1.5 D). The pile researched in this paper (S = 0.83 D) is in the slight impact area.